UHRF1 regulates alternative splicing by interacting with splicing factors and U snRNAs in a H3R2me involved manner. Issue 22 (1st July 2021) - Xu, Peng; Zhang, Lan; Xiao, Yao; Li, Wei; Hu, Zhiqiang; Zhang, Rukui; Li, Jin; Wu, Feizhen; Xi, Yanping; Zou, Qingping; Wang, Zhentian; Guo, Rui; et al.
Abstract: The well-established functions of UHRF1 converge to DNA biological processes, as exemplified by DNA methylation maintenance and DNA damage repair during cell cycles. However, the potential effect of UHRF1 on RNA metabolism is largely unexplored. Here, we revealed that UHRF1 serves as a novel alternative RNA splicing regulator. The protein interactome of UHRF1 identified various splicing factors. Among them, SF3B3 could interact with UHRF1 directly and participate in UHRF1-regulated alternative splicing events. Furthermore, we interrogated the RNA interactome of UHRF1, and surprisingly, we identified U snRNAs, the canonical spliceosome components, in the purified UHRF1 complex. Unexpectedly, we found H3R2 methylation status determines the binding preference of U snRNAs, especially U2 snRNAs. The involvement of U snRNAs in UHRF1-containing complex and their binding preference to specific chromatin configuration imply a finely orchestrated mechanism at play. Our results provided the resources and pinpointed the molecular basis of UHRF1-mediated alternative RNA splicing, which will help us better our understanding of the physiological and pathological roles of UHRF1 in disease development.